The Speech of the Banten Prayascita Ceremony in Welcoming the Birth of a Baby - Ni Wayan Sulastri; Yunidar Yunidar; Arum Pujining Tyas; Mohammad Tahir; Syamsuddin Syamsuddin (Civiliza Publishing, Indonesia., 2026)
Indonesia is a country with extraordinary cultural wealth, reflected in the diversity of traditions and traditional ceremonies that still survive today. This study aims to describe the form, meaning, and function of directive speech used in the Banten Prayascita Ceremony in welcoming the birth of a baby in Pasangkayu Regency, West Sulawesi. The research uses a qualitative descriptive approach with a pragmatic study. The research data is in the form of speech that contains directive speech actions obtained through listening, recording, and recording techniques during the implementation of traditional ceremonies. Data analysis is carried out through the process of data reduction, data presentation, and conclusion drawn. The results of the study showed that there were six forms of directive speech in the Banten Prayascita Ceremony, namely the act of ordering as many as 10 data, requesting 5 data, inviting 3 data, prohibiting 3 data, giving advice 2 data, and requesting 3 data. The act of speaking commands, requests, invitations, prohibitions, and suggestions functions predominantly as a means of regulating social actions of ceremony participants, while the act of pleading functions as a medium of spiritual communication that contains prayers and hopes for the safety of the baby and his family. The meaning contained in each speech is influenced by the cultural context, the purpose of communication, and the customary and religious values that underlie the implementation of the ceremony. The findings of this study show that language in the Banten Prayascita Ceremony not only functions as a means of communication, but also as an instrument for cultural preservation, strengthening social relations, and actualizing the spiritual values of the community.